2016
DOI: 10.1002/cbdv.201500293
|View full text |Cite
|
Sign up to set email alerts
|

On the Permeation by Dioxygen of Urate Oxidase from Aspergillus flavus in Complex with Xanthine Anion: Dioxygen Pathways and a Portrait of the Enzyme Cavities from Molecular Dynamics Simulations in Water Solution

Abstract: This work describes molecular dynamics (MD) simulations in aqueous media for the complex of the homotetrameric urate oxidase (UOX) from Aspergillus flavus with xanthine anion (5) in the presence of dioxygen (O2 ). After 196.6 ns of trajectory from unrestrained MD, a O2 molecule was observed leaving the bulk solvent to penetrate the enzyme between two subunits, A/C. From here, the same O2 molecule was observed migrating, across subunit C, to the hydrophobic cavity that shares residue V227 with the active site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…This whole pattern indicates some preference by the O 2 molecule, albeit toward extremely broad gates, which can also serve for O 2 entrance . Therefore, the results of RAMD simulations contradict speculations that O 2 can have indiscriminate access to the active site from micropores in the four‐helix bundle…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This whole pattern indicates some preference by the O 2 molecule, albeit toward extremely broad gates, which can also serve for O 2 entrance . Therefore, the results of RAMD simulations contradict speculations that O 2 can have indiscriminate access to the active site from micropores in the four‐helix bundle…”
Section: Resultsmentioning
confidence: 91%
“…Our approach to ligand pathways between the bulk solvent and the active site of proteins has long been based on classical molecular dynamics (MD) in aqueous environment . Any such project with diiron proteins was long delayed in view of the heavy computational burden of parameterizing the diiron active site through the bonded model.…”
Section: Resultsmentioning
confidence: 99%
“…The bonded model would be confined to MaL laccase, if successful. Because of such a discouraging perspective, in the framework of our systematic investigation of small‐gas permeation of proteins, an alluring nonbonded dummy‐atom model for Cu(II) that includes the Jahn–Teller effect was developed . This model, developed for single Cu(II) proteins, could also be valid for the complex array of Cu(II) ions of laccases.…”
Section: Resultsmentioning
confidence: 99%
“…The unraveled pathway of O 2 expulsion from the enzyme can also be reasonably assumed to be a pathway for the molecule O 2 from the external solvent to the enzyme active site. To this concern, we have recently shown that the preferred pathway for O 2 expulsion under RAMD from the active site of urate oxidase coincides with the O 2 pathway from the bulk solvent to the enzyme active site under unbiased MD, affording reliability to the RAMD code.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation